Prediction of double stacking hydrocarbon using Marine Controlled Source Electromagnetic method - Rauf, M. (Institute of Electrical and Electronics Engineers Inc., 2015)
In Marine Control Source Electromagnetic (MCSEM) method for Seabed Logging (SBL), different antenna orientations varies the sensitivity in detecting hydrocarbon layer. Up to the recent works, double stacking of hydrocarbon sensitivity has not been addressed. In this article, first we present the challenging oil detect-ability using different orientations of the electric dipole antenna. Our simulation results prevails that the Ex field response by Horizontal Electric Dipole, in-line with receiver (HED-R), is found to be the most sensitive in detecting one hydrocarbon layer, compared to the Vertical Electric Dipole (VED) in the given conditions. Furthermore for every 50m increment of oil layer thickness, 20 of the E-field magnitude is found to be increased. For deep target oil reservior, VED antenna gives the most optimum sensitivity in detecting double stacking of hydrocarbon layer with the highest percentange difference increment of 11.21 compared to both orientations of (HED). Thus with the above contributions, this research opens new doors in the field of efficient oil detection using the respective dipole antenna orientation and challenging resistive layer detection in the offshore environment. Â© 2014 IEEE.